Pengendapan Uranium pada Monasit Bangka sebagai Ammonium Diuranate (ADU) Menggunakan Gas NH3 - Prassanti, Riesna; Fauzan, Ahmad Miftah; Putra, Aditya Widian; Pratama, Afiq Azfar; Dewita, Erlan; Hidayat, Rachmat Fauzi; Ani, Budi Yuli; Permana, Yoga (BRIN Publishing, 2020)
Monazite, as a by-product of tin mining, contains rare earth elements (REE) and radioactive elements like uranium (U) and thorium (Th). The monazite processing Research and Development at the Center for Nuclear Mineral Technology-National Nuclear Energy Agency (PTBGN-BATAN) has succeeded in separating REE as a hydroxide compound with an 85% recovery. The radioactive elements U and Th are each obtained as a product in the form of concentrated compounds of ammonium diuranate (ADU)/(NH4)2U2O7 and thorium hydroxide (Th(OH)4). In previous studies, the separation of U as ADU in monazite was carried out by the precipitation process using NH4OH solution. In this research, U will be precipitated as an ADU using NH3 gas reagents to obtain precipitation optimum conditions. Precipitation feed in the form of (U, Th, REE) sulfate solution derived from the monazite processing using the alkali or base method, which includes decomposition using NaOH, partial dissolution using HCl, and total dissolution using H2SO4. The parameters studied include the effect of NH3 gas flow rate, process temperature, and contact time on U recovery. The results showed that on the static pH-7 condition, the optimum state of U precipitation using NH3 gas is at NH3 gas flow rate of 150 ml/minutes, processing temperature of 30oC, and 15 minutes contact time with precipitation recovery of U 100%, Th 99.97%, and REE 99.93%. These results indicate that U has been taken entirely but still mixed with other elements, which are Th and REE, so that further research is needed to obtain U with high purity on optimum pH condition.